MRI Features of Idiopathic Scrotal Calcinosis: A Case Report - Huang P; Zhu X; Guo L (Dove Medical Press, 2023)
Peng Huang,* Xinyu Zhu,* Li Guo Department of Radiology, The Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, People's Republic of China*These authors contributed equally to this workCorrespondence: Li Guo, Email guolidoc@163.comAbstract: In this study, we report a case of idiopathic cutaneous calcium deposits in the scrotum diagnosed by imaging and pathology. A 31-year-old male presented 4 years ago with multiple nodules on the scrotal skin that had increased significantly in the past 2 years. MR showed mainly low signal nodular shadowing and diagnosed idiopathic cutaneous calcium deposits in the scrotum. To our knowledge, this is one of the rare diagnoses of the disease by imaging presentation.idiopathic scrotal calcinosis, scrotum, MRI